Determinants of Economic Growth in Regencies/Cities in Central Java Province for the Years 2017-2021 - Subakti, Helmi Nisa; Hasmarini, Maulidiyah Indira (Fakultas Ekonomi dan Bisnis Universitas Muhammadiyah Parepare, 2024)
Regional economic growth is a crucial indicator in evaluating the success of a region's development. In Indonesia, regional funding sourced from Local Revenue (Pendapatan Asli Daerah/PAD), General Allocation Funds (Dana Alokasi Umum/DAU), and Revenue Sharing Funds (Dana Bagi Hasil/DBH) plays a vital role in driving economic growth at the district and city levels. This study aims to analyze the impact of PAD, DAU, and DBH on economic growth in districts and cities in Central Java Province during 2017-2021. The research employs panel data regression methods using the Common Effects Model (CEM), Fixed Effects Model (FEM), and Random Effects Model (REM), along with Chow and Hausman tests to select the optimal model. The results indicate that, simultaneously, PAD, DAU, and DBH significantly influence economic growth, with FEM being the most appropriate model. The regression coefficients show that DAU and DBH have a positive impact on economic growth, whereas PAD has a negative impact. These findings suggest that effective management of regional funding sources can enhance economic growth, while suboptimal management of PAD can have adverse effects. This study recommends that local governments strengthen the management of PAD, DAU, and DBH to improve public services and regional economic growth. Future research is encouraged to expand the geographic scope and incorporate more comprehensive variables.